OPTIMALISASI PERAN GURU BIMBINGAN DAN KONSELING DALAM PEMBENTUKAN KARAKTER SISWA - Suroso, Ayu Santika; Salehudin, Mohammad (Fakultas Agama Islam Universitas Wiralodra Indramayu, 2021)
Character education is an educational system that aims to instill certain character values ​​in students in which there is a component of knowledge, awareness or willingness, and actions to carry out these values. The purpose of this research is to find out how important the role of counseling teachers is in shaping the character of students and how to deal with them. This study uses a qualitative approach with a descriptive type that aims to describe the role of the teacher as a role model in developing student character. One way to build character in students is to use the group guidance method. Group Guidance is one of the effective counseling techniques for character building students.